Green Determination of Urea in Moisturizers by Diffuse Reflectance Spectroscopy - Toledo, Paulo Roberto A. Bueno [UNESP]; Toci, Aline Theodoro; Pezza, Helena Redigolo [UNESP]; Pezza, Leonardo [UNESP] (Taylor & Francis, 2017)
This manuscript describes the development and application of a simple, inexpensive, and green method for the quantification of urea in skin moisturizer creams, using a combined spot test/diffuse reflectance spectroscopy procedure. The method is based on the derivatization of urea with a chromogenic reagent (p-dimethylaminocinnamaldehyde) in acidic methanol, yielding a colored compound on the surface of filter paper. The reaction parameters were optimized using chemometric experimental design. Reflectometric measurements of the colored compound were performed at 530 nm, the wavelength of maximum absorption. The linear dynamic range was from 25 to 750 mg L−1. The detection and quantification limits were 6.50 and 21.65 mg L−1, respectively. The method was successfully used for the determination of urea in skin moisturizer creams, demonstrating that it is a reliable eco-friendly alternative.
Keywords: Diffuse reflectance spectroscopy; green analytical methodology; moisturizer cream; spot test; urea